2019
DOI: 10.1002/gj.3514
|View full text |Cite
|
Sign up to set email alerts
|

Provenance of newly discovered Upper Ordovician black rock units in the West Kunlun Orogen, China: Constraints from detrital zircon U–Pb chronology and whole‐rock geochemistry

Abstract: We present new detrital zircon U–Pb chronological and whole‐rock geochemical data for the newly discovered black rock units in West Kunlun Orogen in an attempt to constrain the provenance variations of the siliciclastic rocks and the tectonic history of NW China. Geochemical data indicate these black rock units could have formed in an active continental margin to continental arc setting during the Late Ordovician and source rocks could have undergone modest chemical weathering under a relatively warm and humid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…Owing to their lower mobility in a variety of environments and lesser residence times in seawater (Cox, Lowe, & Cullers, 1995;Taylor & McLennan, 1985), the trace elements and rare earth elements (REEs) are useful in determining the provenance and tectonic settings. Certain immobile trace elements (e.g., V, La, Th, Zr, Hf, Sc, Co, Ni, Cr, and REEs) are used to identify the most likely provenance of a clastic sedimentary rock (Asiedu, Agoe, Amponsah, Nude, & Anani, 2019;Bhatia, 1985;Bhatia & Crook, 1986;Chen et al, 2019;Cullers, 1995;Cullers & Berendsen, 1998;Cullers & Podkovyrov, 2002;Garver & Scott, 1995;Khan, Sarma, Somasekhar, Ramanaiah, & Ramakrishna Reddy, 2019;Ma et al, 2019;Madhavaraju et al, 2020,b;McLennan, 1989;Nagarajan et al, 2014Nagarajan et al, , 2015Nagarajan et al, , 2019Nagarajan, Armstrong-Altrin, et al, 2017;Nagarajan, Roy, et al, 2017).…”
mentioning
confidence: 99%
“…Owing to their lower mobility in a variety of environments and lesser residence times in seawater (Cox, Lowe, & Cullers, 1995;Taylor & McLennan, 1985), the trace elements and rare earth elements (REEs) are useful in determining the provenance and tectonic settings. Certain immobile trace elements (e.g., V, La, Th, Zr, Hf, Sc, Co, Ni, Cr, and REEs) are used to identify the most likely provenance of a clastic sedimentary rock (Asiedu, Agoe, Amponsah, Nude, & Anani, 2019;Bhatia, 1985;Bhatia & Crook, 1986;Chen et al, 2019;Cullers, 1995;Cullers & Berendsen, 1998;Cullers & Podkovyrov, 2002;Garver & Scott, 1995;Khan, Sarma, Somasekhar, Ramanaiah, & Ramakrishna Reddy, 2019;Ma et al, 2019;Madhavaraju et al, 2020,b;McLennan, 1989;Nagarajan et al, 2014Nagarajan et al, , 2015Nagarajan et al, , 2019Nagarajan, Armstrong-Altrin, et al, 2017;Nagarajan, Roy, et al, 2017).…”
mentioning
confidence: 99%
“…Some dark meta-sedimentary rocks have the MDAs of ca. 460 Ma and were deposited in the continental arc setting in the western Tiklik belt [26]. All of the data indicate that the meta-sedimentary rocks from the eastern Tiklik belt are most likely mélanges rather than intact successive stratigraphic units.…”
Section: Provenance Of Meta-sedimentary Rocks In the Eastern Tiklik Beltmentioning
confidence: 89%
“…Therefore, the tectonic relations and isotopic age variations of the Tiklik belt need to be re-evaluated in order to gain a better understanding of the contrasting tectonic senarios. Many researchers have suggested that the Tarim craton is a Rodinia-related piece of orogen that contains evidence of the break-up of the supercontinent [15][16][17][18][19][20][21][22]; however, models of the history of the reconstruction of Tarim in Rodinia are controversial [5,13,16,[22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%